Degradation products of nepafenac ophthalmic suspension and accurate structural characterization of 8-benzoyl-1,2-dihydrocinnolin-3(4H)-one through forced degradation and spectral studies. - Sandeep Zokande; Kavita Inamdar; Amit Gosar; Vikas Mane (Results in Chemistry)
A generic drug product Nepafenac ophthalmic suspension, was manufactured. The generic drug product was filled in the LDPE bottles and stored in stability chambers to determine the shelf life and storage statement. The critical quality attributes of the stability samples were evaluated. It was observed that the content of four unknown degradation products surpassed the identification threshold. Three major unknown degradation products were identified using the mass spectroscopic technique and confirmed by reference standards. The fourth minor unknown degradation product was isolated from the drug product and structurally characterised using UV, FTIR, NMR, and mass spectroscopic techniques, and identified as 8-benzoyl-1,2-dihydrocinnolin-3(4H)-one. It was practically demonstrated that the oxidation of nepafenac leads to the formation of 8-benzoyl-1,2-dihydrocinnolin-3(4H)-one. This degradation study supports a deeper understanding of the degradation products of Nepafenac ophthalmic suspension and will certainly help new applicants to design the specification of Nepafenac ophthalmic suspension during regulatory submission.